Therapeutic effects and underlying mechanism of poly (L-glutamic acid)-g-methoxy poly (ethylene glycol)/combretastatin A4/BLZ945 nanoparticles on Renca renal carcinoma - Chen, Jiaqi; Yin, Min; Yang, Chenguang; Wang, Kun; Ma, Lili; Yu, Haiyang; Huang, Yue; Liu, Feng; Tang, Zhaohui (Frontiers in Bioengineering and Biotechnology, 2024)
The prognosis of advanced renal carcinoma is not ideal, necessitating the exploration of novel treatment strategies. Poly(L-glutamic acid)-g-methoxy poly(ethylene glycol)/Combretastatin A4 (CA4)/BLZ945 nanoparticles (CB-NPs) possess the dual capability of CA4 (targeting blood vessels to induce tumor necrosis) and BLZ945 (inducing M2 macrophage apoptosis), thereby inhibiting tumor growth. This study demonstrated that CB-NPs could inhibit the growth of Renca cells and subcutaneous tumors in mice, with an impressive tumor inhibition rate of 88.0%. The underlying mechanism was explored by western blot analysis, immunohistochemistry, flow cytometry, and other techniques. Results suggested that CB-NPs can induce necrosis in renal carcinoma cells and tissues, downregulate VEGFA expression, promote renal carcinoma cell apoptosis, and reduce the polarization of M2 macrophages. These findings offer innovative perspectives for the treatment of advanced renal carcinoma.